Effects of Cervical Rotation on Hemodynamics in Vertebral Arteries - Ozdemir, Huseyin; Cihangiroglu, Mutlu; Berilgen, Said; Bulut, Serpil (Sage Publications Inc, 2005)
The purpose of this study was to assess the effects of cervical rotations on flow velocity and volumes of vertebral arteries in healthy individuals and patients with cervical spondylosis and vertebrobasilar insufficiency. Twenty-eight patients with degenerative changes in the cervical spine (group 1), 24 patients with clinically proven vertebrobasilar insufficiency (group 2), and 20 healthy individuals (group 3) were evaluated. Significant difference was found in flow velocities of both vertebral arteries during neutral, 30-degree, 60-degree, and maximum rotations between groups 1 to 3 and groups 2 to 3. No significant difference was observed in flow velocities and volumes of the vertebral artery between groups 1 and 2. This occurrence might be explained by the fact that both groups have been affected not only by atherosclerotic changes but also by external pressure due to degenerative changes in the cervical spine.
Keywords: cervical spondylosis; cervical rotation; vertebral artery; vertebrobasilar insufficiency; Doppler ultrasound